Molecular diversity of anticoagulants from haematophagous animals - Koh, Cho Yeow; Kini, R. Manjunatha (Thrombosis and Haemostasis, 2009)
To obtain blood meals, haematophagous animals are armed with potent pharmacological molecules to overcome several of their hosts’ response systems. Among them, a large number of exogenous anticoagulants which target the haemostatic system have been identified and characterised. Studies on these anticoagulants have expanded our knowledge on the blood coagulation system, and provided a valuable source of antithrombotic therapeutic agents. Advances in genomic, transcriptomic, structural and proteomic tools greatly accelerated the discovery and analysis of the exogenous anticoagulants in recent years. The molecular diversity observed in these molecules is huge and is constantly expanding. In this review, we will provide an overview on the structure, function and mechanism of the exogenous anticoagulants from haematophagous animals and rationalise their molecular diversity.
Keywords: Anticoagulants; haematophagous animals; structure-function relationships; exogenous factors; molecular diversity